A hepatitis B virus-derived peptide combined with HBsAg exerts an anti-HBV effect in an HBV transgenic mouse model as a therapeutic vaccine - Choi, Yu-Min; Kim, Dong Hyun; Jang, Junghwa; Kim, Bum-Joon (Frontiers in Immunology, 2023)
For complete or functional cure of hepatitis B virus (HBV) infection, application of immunotherapy is now being attempted. Recently, we reported that a 6-mer hepatitis B virus (HBV)-derived peptide, Poly6, exerts a strong anticancer effect in tumor-implanted mice through inducible nitric oxide synthase (iNOS)-producing DCs (Tip-DCs) in a type 1 interferon (IFN-I)-dependent manner, suggesting its potential as a vaccine adjuvant. Therefore, in this study, we explored the potential of Poly6 in combination with HBsAg as a therapeutic vaccine against hepatitis B virus infection. To this end, we investigated the immunotherapeutic potential of Poly6 combined with HBsAg vaccination against hepatitis B virus infection in C57BL/6 mice or an HBV transgenic mouse model. In C57BL/6 mice, Poly6 enhanced DC maturation and DC migration capacity in an IFN-I-dependent manner. Moreover, the addition of Poly6 to alum in combination with HBsAg also led to enhanced HBsAg-specific cell-mediated immune (CMI) responses, suggesting its potential as an adjuvant of HBsAg-based vaccines. In HBV transgenic mice, vaccination with Poly6 combined with HBsAg exerted a strong anti-HBV effect via induction of HBV-specific humoral and cell-mediated immune responses. In addition, it also induced HBV-specific effector memory T cells (TEM). In conclusion, our data indicated that vaccination with Poly6 in combination with HBsAg exerts an anti-HBV effect in HBV transgenic mice, which is mainly mediated by HBV-specific CMI and humoral immune responses via IFN-I-dependent DC activation, suggesting the feasibility of Poly6 as an adjuvant for an HBV therapeutic vaccine.